On the evaluation of the pressure coefficient of the surface tension of liquids by measurements of the velocity of ultrasonic waves - SOCZKIEWICZ, Eugeniusz (Archives of Acoustics, 1977)
A formula has been derived to evaluate the pressure coefficient (∂σ/∂p)r of the surface tension by measuring the velocity of propagation of ultrasonic waves. It was found that the calculated values of this coefficient are in good agreement with the experimental data obtained by other authors. The values of the coefficients (∂σ/∂p)_T and σ^{-1}(∂σ/∂p)T have been calculated for a number of liquids. The results obtained permitted us to determine the density of the surface layer of a liquid at the interface with gas. For saturated hydrocarbons and alcohols both the value of the coefficient σ^{-1}(∂σ/∂p)_T and the percentage reduction of the density, of the surface layer in relation to the liquid density decrease monotonically with the increasing length of the chains of molecules in a given chemical compound.